ANALISIS PENDEKATAN PEMBELAJARAN BERDIFERENSIASI BERBASIS PROBLEM BASED LEARNING MATA PELAJARAN IPAS KELAS IVA SDN BENDUNGAN SEMARANG - Wahyuni, Selvy; Miyono, Noor; Mayasari, Luthfaida; Hayat, M. Syaiful (INOPENDAS: Jurnal Ilmiah Kependidikan, 2025)
This study aims to accommodate or meet students' learning needs by implementing Problem Based Learning (PBL)-based differentiation learning in the IVA Class IVA Science subject at SDN Bendungan Semarang. This study was conducted from January 22 to February 7, 2024 with the research subjects of all IVA class students totaling 27 children. This research is a qualitative study with a descriptive approach through interviews, documentation and observation. The data validation technique uses time triangulation, source triangulation, technical triangulation or member checking. The data analysis technique for this study uses an interactive model consisting of data reduction, data presentation, and drawing conclusions. The findings of this study show how differentiation learning in class IVA accommodates various learning preferences or diversity of learning styles. It is proven that students' learning styles show 33% kinesthetic, 30% auditory, and 37% visual from the results of the diagnostic assessment. Through varied learning with student-centered learning styles, it can be facilitated by the application of differentiated learning. Differentiated learning based on Problem Based Learning (PBL) is very effective and supports students to develop their conceptual and cognitive understanding in solving problems.